LEGAL REGULATION OF ELECTRONIC IDENTIFICATION AND ELECTRONIC TRUST SERVICES IN UKRAINE: PROSPECTS FOR IMPROVEMENT AND DEVELOPMENT UNDER THE CONDITIONS OF HARMONIZATION WITH THE LAW OF THE EUROPEAN UNION - Vovk Mariіa; Zaiats, Olha; Yurkevych, Yurii (Socio-economic relations in the digital society, 2024)
The use and exchange of electronic documents certified by an electronic signature and seal are increasingly used in all spheres of society. In the field of private legal relations, it speeds up the procedure for concluding contracts. Increasing the efficiency of their signing, in turn, allows you to speed up the execution of contractual relations and thereby improve the quality of service to customers, partners, and suppliers. Legal regulation is analyzed in the article on electronic identification and electronic trust services. Emphasis is placed on the importance of harmonizing current legislative norms in Ukraine with the legal norms of the European Union within the indicated scientific limits of the study. Attempts to implement the experience of international standards regarding electronic identification and electronic trust services into national legislation are analyzed. The article examines the concepts of electronic signature and electronic seal and analyzes their types: improved electronic signature and seal, and qualified electronic signature and seal. Attention is also focused on those requirements that are strictly subject to the qualification of an electronic signature and seal. Within the framework of the study of current legislation in general and court practices in particular, the legal consequences in cases of the absence of an electronic signature or seal on electronic documents have been clarified. For example, in cases where there is no electronic signature or seal on electronic documents, it becomes impossible to identify the sender of a particular message. Instead, in such a case, it is appropriate to note the lack of protection of this type of document from the possibility of text correction or editing. Therefore, it was established that in the case of the absence of an electronic signature or seal in an electronic document, such a document cannot be considered in the court process as evidence. The position is supported that, at the national level, a contract signed between the parties without the use of a qualified electronic signature will not mean the invalidity of such a contract, therefore the use of ordinary and improved electronic signatures is completely legal and will create rights and obligations for the parties who signed such a contract.